Influence of Platelet Membrane Sialic Acid and Platelet-Associated IgG on Ageing and Sequestration of Blood Platelets in Baboons - Kotzé, H F; Wyk, V van; Badenhorst, P N; Heyns, A du P; Roodt, J P; Lötter, M G (Thrombosis and Haemostasis, 1993)
Platelets were isolated from blood of baboons and treated with neuraminidase to remove platelet membrane sialic acid, a process which artificially ages the platelets. The platelets were then labelled with 111In and their mean life span, in vivo distribution and sites of Sequestration were measured. The effect of removal of sialic acid on the attachment of immunoglobulin to platelets were investigated and related to the Sequestration of the platelets by the spleen, liver, and bone marrow. Removal of sialic acid by neuraminidase did not affect the aggregation of platelets by agonists in vitro, nor their sites of Sequestration. The removal of 0.51 (median, range 0.01 to 2.10) nmol sialic acid/108 platelets shortened their life span by 75 h (median, range 0 to 132) h (n = 19, p <0.001), and there was an exponential correlation between the shortening of the mean platelet life span and the amount of sialic acid removed. The increase in platelet-associated IgG was 0.112 (median, range 0.007 to 0.309) fg/platelet (n = 25, p <0.001) after 0.79 (median, range 0.00 to 6.70) nmol sialic acid/108 platelets was removed (p <0.001). There was an exponential correlation between the shortening of mean platelet life span after the removal of sialic acid and the increase in platelet-associated IgG. The results suggest that platelet membrane sialic acid influences ageing of circulating platelets, and that the loss of sialic acid may have exposed a senescent cell antigen that binds IgG on the platelet membrane. The antibody-antigen complex may then provide a signal to the macrophages that the platelet is old, and can be phagocytosed and destroyed.